DIMENSI SOSIAL FOTO SELFIE DALAM PERSPEKTIF SEMIOLOGI ROLAND BARTHES - Maharani Putri, Anak Agung Chintya; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2018)
ABSTRACT This study attempts to examine the social dimension contained in various selfie photos, for instance; selfie photo of the public, celebrity, endorse or promotion, academician, and politician. The approach used in this study is a qualitative approach by using literature study. The theory and method used in this study are the semiology of Roland Barthes. Roland Barthes's theory and semiology method consist of one-tier semiology in the form of denotative image and two-tier semiology that contains connotative image. In each layer of semiology there is still other semiological elements. Based on the research that has been done, every selfie photo that is generally considered normal, apparently contains a rich code if analysed through a semiological perspective of Roland Barthes. In addition, various elements contained in Roland Barthes's semiology are able to show various dimensions contained in selfie photos, including psychological, cultural and particularly social dimension. Furthermore, this research shows that the richest selfie photo code is found in celebrity selfie photo, while the poorest selfie photo code is found in academician photo. Additionaly, most of the selfie photos studied tend to converge their form as a paradox, namely in celebrity selfie photo, endorse, and academician. While selfie photo of the public and politician converge their form as a paradoxical representation. Suggestions in this study are, the selfie actor should be careful in displaying the code in the selfie image since the codes can be interpreted freely by other parties so that it generates a different meaning from the intended initial meaning. Keywords: Code, Selfie Photo, Semiology